Effects of nitric oxide on growth of maize seedling leaves in the presence or absence of ultraviolet-B radiation - An, Lizhe (Journal of plant physiology, 2005)
The leaves of maize seedlings were used to measure leaf biomass including leaf length, width and weight, and to examine the relationship between nitric oxide (NO) synthase activity in microsomes and cytosol to the exo- and endo-beta-glucanase activity during growth. It was found that ultraviolet-B radiation (UV-B radiation) strongly induced nitric oxide synthase (NOS) activity but caused both a decrease of leaf biomass and exo- or endo-beta-glucanase activity. In contrast, the NOS inhibitor and NO donor largely decreased the activity of NOS in non-irradiated seedlings. The inhibitor also reduced exo- and endo-beta-glucanase activity and leaf biomass while the donor increased the enzyme activity and leaf biomass under normal conditions. Alternatively, under ultraviolet-B, the additional inhibitor of NOS and NO donor appeared to compromise the effects of ultraviolet-B on glucanase activity and leaf biomass, making the relationship between NOS activity and glucanase activity negatively correlated. This suggests that the changes of NOS activity showed a positive correlation to glucanase activity and leaf biomass in the absence of ultraviolet-B, but a negative correlation to ultraviolet-B irradiation and NO donor treatment alone. It is assumed that exo- and endogenous NO is responsible for the up-regulation of regular growth and development without ultraviolet-B. Under UV-B radiation, however, it might function as a signaling molecule of ultraviolet-B inhibiting leaf growth of maize seedlings to carry out stress-signaling transduction